White matter correlates of apathy in HIV-positive subjects: a diffusion tensor imaging study - Hoare, Jacqueline; Fouche, Jean-Paul; Spottiswoode, Bruce; Joska, John A; Schoeman, Renata; Stein, Dan J; Carey, Paul D (The journal of neuropsychiatry and clinical neurosciences, 2010)
Apathy is commonly reported by patients infected with HIV. No previous work has assessed the relationship between white matter and apathy in HIV. The authors aimed to determine whether apathy in HIV reflects a direct effect of the virus on subcortical brain regions or a secondary neuropsychiatric symptom. Thirteen HIV+ participants with apathy, 13 HIV+ participants with no apathy, and 10 healthy comparison subjects were examined using diffusion tensor imaging in the region of the anterior cingulate and corpus callosum. Results of the study confirmed the hypothesis which anticipated changes associated with apathy in white matter tracts that relay through the medial prefrontal cortex.